(untitled) (Journal of Educational Sciences, 2022)
The use of authentic materials is the most common and accessible source of language and culture learning in English as a foreign language classes. However, with the rapid growth of the use of innovative technologies and the Internet in the field of education, the amount of unwanted content in media resources is growing. Since authentic material is an extremely important component of a foreign language lesson, media-discursive competence should become one of the potential materials for teaching and learning English. Based on this assumption, this study was developed for qualitative study of the possibility of using the integration of media-discursive competence in the teaching materials of English classes. The article presents an online survey of teachers and students of the «School-Lyceum No. 71» of the Astana city to study personal attitudes to the use of media discursive materials in the classroom; a test before and after learning English to measure students’ conversational skills after class. The data were collected using an open questionnaire, an online survey in Google Forms; models and topics were summarized and formed based on data analysis. The results showed that teachers and students were motivated to learn English using media-discursive materials and consider it mandatory in the curriculum. The results can serve as a guide for teachers interested in developing classes that improve students’ media-discursive competence. In addition, the results of this study can be used as a guide for further research. Keywords: media literacy, media text, advertising, authentic material.